Recombinant FGF21 Protects Against Blood-Brain Barrier Leakage Through Nrf2 Upregulation in Type 2 Diabetes Mice - Yu, Zhanyang; Lin, Li; Jiang, Yinghua; Chin, Ian; Wang, Xiaojie; Li, Xiaokun; Lo, Eng H.; Wang, Xiaoying (Molecular neurobiology, 2019)
Blood-brain barrier (BBB) damage is a characteristic feature of diabetes mellitus pathology and plays significant roles in diabetes-associated neurological disorders. However, effective treatments for diabetes targeting BBB damage are yet to be developed. Fibroblast growth factor 21 (FGF21) is a potent regulator of lipid and glucose metabolism. In this study, we tested the hypothesis that recombinant FGF21 (rFGF21) administration may reduce type 2 diabetes (T2D)-induced BBB disruption via NF-E2-related factor-2 (Nrf2) upregulation. Our experimental results show that rFGF21 treatment significantly ameliorated BBB permeability and preserved junction protein expression in db/db mice in vivo. This protective effect was further confirmed by ameliorated transendothelial permeability and junction protein loss by rFGF21 under hyperglycemia and IL1β (HG-IL1β) condition in cultured human brain microvascular endothelial cells (HBMEC) in vitro. We further reveal that rFGF21 can activate FGF receptor 1 (FGFR1) that increases its binding with Kelch ECH-associating protein 1 (Keap1), a repressor of Nrf2, thereby reducing Keap1-Nrf2 interaction leading to Nrf2 release. These data suggest that rFGF21 administration may decrease T2D-induced BBB permeability, at least in part via FGFR1-Keap1-Nrf2 activation pathway. This study may provide an impetus for development of therapeutics targeting BBB damage in diabetes.